Research on human health Status assessment system of pulse data collection and analysis before and after exercise - Luyao Zhang; Xianfeng Cai (Elsevier, 2020)
In order to better assess the health of the human body and protect people from disease, this study designs a wearable glasses system based on pulse signal preprocessing algorithm, pulse rate calculation algorithm and motion recognition algorithm. The pulse data before and after exercise are used to analyze the health status of the human body. Finally, the performance in various aspects of the system was verified by relevant experiments. The results show that the system is feasible. It can be seen that the system can be used for the assessment of human health conditions, and it is expected to serve people well in the future and make people live a healthier life.